PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN: Studi Empiris pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia Tahun 2011-2015 - Fransisca Pangestu Wardani; Zulkifli Zulkifli (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2017)
This study aims to determine the effect of good corporate governance to financial performance of companies listed on the Indonesia Stock Exchange Year 2011-2015. Good Corporate Governance in this study is proxied in the Proportion of Independent Commissioner Board, Audit Committee Size, Size of Board of Directors, Board of Commissioners size. The financial performance of proxies in ROA. The sampling method using purposive sampling method. The population of 143 companies listed in the Indonesia Stock Exchange in 2015, then obtained a sample totaling 56 companies, so the amount of data used as many as 280 data. The analytical tool used (1) Descriptive statistics (2) Classical Assumption Test: Normality Test, Test Linearity, Test multicoloniarity, Autocorrelation test and test Heteroskidastity (3) Regression Analysis: The coefficient of determination (R²), Test Statistic F, and test statistics t. The results showed that the variable proportion of independent board has no effect on the financial performance measured by ROA. The size of the variable audit committee has no effect on the financial performance is measured using ROA. The size of the variable board of directors affect the financial performance is measured using ROA. The size of the variable board of directors has no effect on the financial performance is measured using ROA. Based on the results of the F test analysis showed that the proportion of independent board, the size of the variable audit committee, the size of the board of directors and board size together not significant effect on ROA, or it could be concluded that good corporate governance is not a significant effect on the financial performance of the company.